2023
DOI: 10.1093/genetics/iyad135
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNAs contribute to DNA damage resistance in Arabidopsis thaliana

Abstract: Efficient repair of DNA lesions is essential for faithful transmission of genetic information between somatic cells and for genome integrity across generations. Plants have multiple, partially redundant and overlapping DNA repair pathways, probably due to the less constricted germline and the inevitable exposure to light including higher energy wavelengths. Many proteins involved in DNA repair and their mode of actions are well described. In contrast, a role for DNA damage-associated RNA components, evident fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 72 publications
3
10
2
Order By: Relevance
“…Differently for Durut et al. (2023), we did not observe an effect on leaf development of Δlinda seedlings following zeocin treatment but noticed a severe cell death response in the root meristem. This increased cell death may account for the observed reduction in root growth recovery following transfer of the Δlinda seedlings from genotoxic to control conditions, compared to control plants.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Differently for Durut et al. (2023), we did not observe an effect on leaf development of Δlinda seedlings following zeocin treatment but noticed a severe cell death response in the root meristem. This increased cell death may account for the observed reduction in root growth recovery following transfer of the Δlinda seedlings from genotoxic to control conditions, compared to control plants.…”
Section: Discussioncontrasting
confidence: 97%
“…We found LINDA to be strongly induced by different stresses inducing primarily DSBs, including zeocin and bleomycin, by UV‐C, which causes predominantly the formation of pyrimidine‐dimers, as well as by X‐rays (Wang et al., 2016) and gamma‐rays (Bourbousse et al., 2018). Similarly, LINDA was recently found in comparative RNA‐Seq analysis (Durut et al., 2023). The pyrimidine dimers caused by UV‐C can be either directly reversed by photoreactivation (Jiang et al., 1997) or removed by nucleotide excision repair (NER).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Not only is LINDA needed for the regulation of its flanking gene, but also for the fine-tuning of the DDR after the occurrence of DNA double-strand breaks. Another study confirmed the involvement of LINDA in DDR and studied three additional lncRNAs in Arabidopsis 30 . One of these studied lncRNAs, annotated on Araport11 as a novel transcribed region (AT4G09215), was strongly upregulated by UV-C irradiation.…”
Section: Introductionmentioning
confidence: 75%
“…RLFS_026432 was found to be one of the most highly induced lncRNAs upon DNA damage caused by X-rays or UV-C 28,30 . To determine the optimal conditions for its induction by UV-C, different doses were tested and expression of RLFS_026432 was measured after 3 hours, the same time frame as in Wang et al (2016) 28 .…”
Section: Rlsf_026432 Is Induced In Response To Dna Damagementioning
confidence: 99%